Management of Hereditary Transthyretin Amyloidosis (ATTRv) Patients and Asymptomatic Carriers in Spain: The EMPATIa Study - Losada López, Inés; Gonzalez-Moreno, Juan; Buades Reinés, Juan; Sevilla, Teresa; Martinez Valle, Fernando; Galán Dávila, Lucía; Muñoz Beamud, Francisco; Bárcena Llona, José Eulalio; Romero Acebal, Manuel; Tarilonte, Patricia; Setaro, Francesca (Journal of clinical medicine, 2024)
Background: Hereditary transthyretin amyloidosis (ATTRv) is an autosomal-dominant systemic disease, where amyloid fibrils accumulate especially in the peripheral and autonomic nervous systems and in the heart. The aim of the present work was to outline the follow-up and type of management received by asymptomatic carriers (ACs) and Coutinho stage 1 ATTRv patients in Spain. Methods: A cross-sectional, non-interventional study was conducted throughout seven experienced hospitals in Spain. A total of 86 ACs without neurological symptoms and 19 Coutinho stage 1 ATTRv patients diagnosed 12 months before their enrollment were included. Clinical and demographic data, red flags, and neurological and cardiological evaluations were gathered. In addition, site variables were collected from four centers to describe the clinical management of ATTRv. Results: ATTRv clinical management varied depending on the center setting but was primarily overseen by neurology and internal medicine, which were responsible for the holistic follow-up of ACs and patients. Routinely, neurologists, neurophysiologists, cardiologists, and internal medicine conducted the follow-up. Specialties involved in initial AC assessment were neurophysiologists and cardiologists in 100% of cases, neurologists (75%), internists and geneticists (50%), and ophthalmologists (25%). A review of the medical tests performed proved an exhaustive management of the study population. Stable patients were followed up every 6 months, while those under evolution were monitored every 3–6 months. The frequency of monitoring of ACs was annual, and carriers classified with doubtful disease onset were visited every 3–6 months. Conclusions: The EMPATIa study provides valuable insights into the management of ATTRv in a real-world clinical setting in highly experienced hospitals in Spain. It demonstrates that multidisciplinary practice and enhanced disease awareness may lead to a reduction in diagnostic delay.